2006
DOI: 10.1111/j.1365-3083.2006.01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐Mediated Regulation of the Immune Response

Abstract: Antibodies administered in vivo together with the antigen they are specific for can regulate the immune response to that antigen. This phenomenon is called antibody‐mediated feedback regulation and has been known for over 100 years. Both passively administered and actively produced antibodies exert immunoregulatory functions. Feedback regulation can be either positive or negative, resulting in >1000‐fold enhancement or >99% suppression of the specific antibody response. Usually, the response to the entire anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 89 publications
1
95
1
2
Order By: Relevance
“…The activation of Agspecific T cells allows for subsequent enhancement of cognate B and T cells to cross-talk and expand. This immunostimulatory effect of CD23-bound IgE is similar to a strong adjuvant and is Ag-specific in mice (11).…”
mentioning
confidence: 88%
“…The activation of Agspecific T cells allows for subsequent enhancement of cognate B and T cells to cross-talk and expand. This immunostimulatory effect of CD23-bound IgE is similar to a strong adjuvant and is Ag-specific in mice (11).…”
mentioning
confidence: 88%
“…Specific Abs have a profound influence on Ab responses (40,41). Protein Ag in the form of ICs with IgM Abs is typically more potent than free Ag in promoting Ab responses (40).…”
Section: Discussionmentioning
confidence: 99%
“…With IgG Abs, this enhancement was mainly observed with soluble protein Ags, whereas responses against particulate Ags were suppressed (41). This dual effect was dependent on the nature of the Ag, as the same anti-hapten Ab was able to enhance or suppress Ab responses when the hapten was conjugated to a soluble protein or particulate Ag, respectively (42).…”
Section: Igg Abs Target Viral Particles For Phagocyte Uptake and Inhimentioning
confidence: 99%
“…Enhanced specific T-cell responses have been observed after treatment with Mucin 1 [5] and HER2/neu- [6] specific antibodies in humans and after injection of neu-specific antibodies in mice that received a neu-expressing whole cell vaccine [7]. It is well established that antibodies administered in vivo together with their specific antigen can regulate the antigen-specific immune response via antibody-mediated feedback regulation [8]. Although it has been shown that IgG can enhance antibody responses and CD4 + T-cell responses via this process [9], enhancement of CD8 + T-cell responses by antibodies remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%